RETRACTED: Effects of Dexmedetomidine on Postoperative Delirium and Expression of IL-1β, IL-6, and TNF-α in Elderly Patients After Hip Fracture Operation - Zhang, Wenchao; Wang, Tianlong; Wang, Geng; Yang, Minghui; Zhou, Yan; Yuan, Yi (Frontiers in Pharmacology, 2020)
Objective: Postoperative delirium (POD) is a common surgical complication in elderly patients. This study investigated the effects of dexmedetomidine on POD and inflammatory factors in elderly patients with hip fracture. Method: The randomized, double-blind, controlled trial enrolled patients aged ≥65 years who underwent operation for hip fracture in the Department of Anesthesiology in Beijing JiShuiTan Hospital from October 2016 to January 2017. The patients were divided into the DEX group and the NS group and were intravenously infused with dexmedetomidine or an equal volume of normal saline, respectively. After surgery, the incidence of delirium at postoperative day 1 (T1), day 2 (T2) and day 3 (T3) were assessed using the Ramsay score and Confusion Assessment Method (CAM) delirium scale. Interleukin (IL)-1, IL-6 and tumor necrosis factor (TNF)-α concentrations in the venous blood of the two groups of patients were detected at T0 (before surgery), T1 and T3. Results: Data from 218 patients were analyzed with 110 patients in the DEX group and 108 in the NS group. Dexmedetomidine decreased POD incidence (18.2% vs. 30.6%, P=0.033). Compared to T0, all three inflammatory factors increased at T1 and then decreased at T3 and changes with time were significant (all P<0.001). IL-6 (P<0.001) and TNF-α (P=0.003) levels were lower in the DEX group, but IL-1 levels were similar. The rate of adverse events was similar in the two groups. Conclusion: Dexmedetomidine reduced the incidence of POD in elderly patients with hip fracture at an early stage, and reduced short-term IL-6 and TNF-α concentrations.